PENGGUNAAN MEDIA PEMBELAJARAN AUGMENTED REALITY DALAM MENSTIMULASI KEMAMPUAN MENGENAL HURUF HIJAIYAH ANAK - Suciati; Sukrin; Syahru Ramadhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low proficiency of young children in recognizing the Hijaiyah letters, which form an essential foundation for learning to read the Qur’an. This situation is evident at Family Kananta Kindergarten, where some children still struggle to distinguish letter shapes and pronounce them correctly. To address this issue, teachers have implemented an innovative learning approach by utilizing Augmented Reality (AR)-based learning media, which is expected to stimulate children’s abilities in a more engaging, interactive, and enjoyable manner. The use of this technology not only displays letters visually in two dimensions but also in three-dimensional forms that can move and are accompanied by the correct pronunciation, allowing children to learn through multisensory experiences. The objective of this study is to determine the implementation methods and the effectiveness of using Augmented Reality-based learning media in improving children’s ability to recognize Hijaiyah letters at Family Kananta Kindergarten. The research design employed was descriptive qualitative research, with the primary data sources being the teachers and children in Group B at Family Kananta Kindergarten. Data were collected through observation, interviews, and documentation, and then analyzed using the Miles and Huberman analytical model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that the implementation of AR media is effective when carried out through several stages: introduction to the media, demonstration of 3D letters, play-based learning activities, fine motor skill development, and interactive assessment via digital quizzes. The use of this media has been proven to significantly improve children’s focus, memory, pronunciation, and motivation. Thus, AR media serves as an effective and relevant educational innovation in stimulating basic Quranic reading skills among young children.